Development of a low–cost γ–ray spectrometry PMT adapter - Andrikopoulos, C.; Zagoraios, G.; Mertzimekis, T. J.; Tsilis, E.; Nistazakis, H. E. (HNPS Advances in Nuclear Physics, 2019)
A crucial part of any scintillator–based spectroscopy experiment is the photomultiplier tube (PMT) and its associate electronics, typically coming in the form of a PMT adapter responsible for amplifying and digitizing the record pulses. Commercial adapters are typically expensive, therefore a more practical and costless solution is in dire need. In the present work, a light–weight, portable electronic circuit was constructed from scratch based on the open–access Theremino design [1] to play the role of a PMT adapter responsible for the processing of the PMT output signal. The adapter is universally compatible with PMTs and with any computer with a built–in sound card. The PC sound card acts as the digitizer of the signal, which is subsequently analyzed by the Theremino MCA analysis software [1]. The construction of this handmade, easily reproducible circuit, increases drastically the ability to perform spectroscopy measurements with the currently available scintillators in our lab.